PERANCANGAN MANAJEMEN BANDWIDTH MENGGUNAKAN MIKROTIK ROUTER WIRELESS PADA SEKOLAH MENEGAH KEJURUAN NEGERI 4 KOTA BENGKULU - Koko Ayun Sundara; Hari Aspriyono; Reno Supardi (Jurnal Media Infotama, 2022)
ABSTRAC This study aims to conduct Bandwidth Management Design Using a Wireless Router Mikrotik at SMKN 4 Bengkulu City to carry out activities that occur on the wifi network at SMKN 4 Bengkulu City. And also as one of the requirements to obtain a bachelor's degree in informatics Study Program, The University of Dehasen Bengkulu. The research method used is the Network Development Life Cycle (NDLC) method which aims at the development process by designing a bandwidth management system using the Mikrotik RB951Ui-2HnD. The design process is how to connect Mikrotik with a computer and then create a network division for Staff, Admin, Teachers and Students using the Winbox application. Mikrotik can do bandwidth management well on the Wi-Fi network at SMKN 4 Bengkulu City with the results of network sharing and display of user logins and passwords so that it can be easier and more organized. Keywords: Bandwidth Management, Mikrotik, Winbox.